Primary Sclerosing Cholangitis: From Pathogenesis to Medical Management - Bunchorntavakul, MD, Chalermrat; Tanwandee, MD, Tawesak; Charatcharoenwitthaya, MD, Phunchai; Reddy, MD, K. Rajender (North American Journal of Medicine and Science, 2012)
Primary sclerosing cholangitis (PSC) is a cholestatic liver disease characterized by progressive inflammatory destruction of intrahepatic and extrahepatic bile ducts. It is strongly associated with inflammatory bowel disease, particularly ulcerative colitis. The pathogenesis of PSC remains unclear, however several hypotheses have been proposed that suggest roles for autoimmunity, genetic susceptibility, and the interaction between microorganisms and host immune response directed at the biliary system. A diagnosis of PSC is based on a constellation of clinical, biochemical, and typical cholangiographic features and usually without the need for liver histopathology. Complications of PSC include pruritus, portal hypertension, bone disease, end-stage liver disease, and cancers. Cholangiocarcinoma eventually develops in 8-15% of PSC patients. A variety of drugs have been evaluated as therapy for PSC, but no therapy has yet been proven to prolong survival or improve outcomes in PSC. Ursodeoxycholic acid (UDCA) has been intensively investigated to address its efficacy in PSC. A recent investigation noted that high-dose UDCA therapy in PSC did not confer benefit on combined clinical and survival endpoints. . Immunosuppressive agents are generally ineffective. Liver transplantation remains the only proven long-term treatment for advanced PSC, with approximately 20-25% risk of disease recurrence. Cancer surveillance, management of cirrhotic complications, and treatment of manifestations of cholestasis in those with PSC are clinically relevant. Further understanding of the pathogenesis of PSC is desperately required in order to effectively improve our current approaches to the management of this disease.